IMPLEMENTASI PRINSIP GOOD CORPORATE GOVERNANCE PADA BANK SYARIAH DI INDONESIA - Nona Azzahra Nasution; Tri Ibnu Ramadhanu; Nurul Fadilah; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
: This study analyzes the implementation of Good Corporate Governance (GCG) principles in Indonesian Islamic banks through qualitative document analysis of annual reports from BSI, BJB Syariah, and BCA Syariah for 2022-2025. Findings reveal GCG implementation at